2016
DOI: 10.1099/jmmcr.0.005039
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis in Mediterranean spotted fever: a case report and a review of the literature

Abstract: Introduction:Mediterranean spotted fever (MSF) is a tick-borne acute febrile disease caused by Rickettsia conorii. Most cases follow a benign course, with a case fatality rate of 3–7 % among hospitalized patients. Complications are described mainly in adult patients and include hepatic, renal, neurological and cardiac impairment. Among cardiac complications, pericarditis, myocarditis and heart rhythm disorders are uncommon complications in MSF and only a few cases have been reported in the literature.Case Pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
(14 reference statements)
1
9
0
1
Order By: Relevance
“…The typical signs of these rickettsioses, with the formation of papules, petechiae and rash, are a direct consequence of the colonization and damage of the vascular endothelium by these pathogens. MSF may be complicated by cardiac symptoms (coronary artery ectasia, myocarditis and atrial fibrillation), ocular symptoms (uveitis, retinal vasculitis and retinopathy), neurological symptoms (cerebral infarction, meningoencephalitis have been reported and, sensorineural hearing loss), pancreatic involvement, splenic rupture and acute renal failure, and by hemophagocytic syndrome [ 146 , 148 , 149 , 150 , 151 , 152 , 153 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 ]…”
Section: Discussionmentioning
confidence: 99%
“…The typical signs of these rickettsioses, with the formation of papules, petechiae and rash, are a direct consequence of the colonization and damage of the vascular endothelium by these pathogens. MSF may be complicated by cardiac symptoms (coronary artery ectasia, myocarditis and atrial fibrillation), ocular symptoms (uveitis, retinal vasculitis and retinopathy), neurological symptoms (cerebral infarction, meningoencephalitis have been reported and, sensorineural hearing loss), pancreatic involvement, splenic rupture and acute renal failure, and by hemophagocytic syndrome [ 146 , 148 , 149 , 150 , 151 , 152 , 153 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 ]…”
Section: Discussionmentioning
confidence: 99%
“…Rickettsia helvetica is known to cause noneruptive infections like in our case [6]. Few cases of myocarditis, pericarditis, atrial fibrillation, and ectasia of coronary arteries have been reported due to R. conorii infections worldwide [16, 17]. According to Colomba et al [16], there had been only one case report of myocarditis due to SFG rickettsia infection from Asia up to 2016.…”
Section: Discussionmentioning
confidence: 82%
“…Few cases of myocarditis, pericarditis, atrial fibrillation, and ectasia of coronary arteries have been reported due to R. conorii infections worldwide [16, 17]. According to Colomba et al [16], there had been only one case report of myocarditis due to SFG rickettsia infection from Asia up to 2016. Nevertheless, we found a past report in a local journal on myocarditis due to rickettsioses from the Western Province of Sri Lanka, but the infecting organism (whether Orientia tsutsugamushi or SFG rickettsia) had not been clearly mentioned there [18].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, atypical forms can be observed with multiorgan involvement including hepatic, renal, neurological and cardiac impairment. [1][2][3][4] We here in report a difficult diagnosis of rickettsiosis occuring after hemorrhagic fever. We also describe EN-FACE-OCT rickettsiosis retinal findings and emphasize the importance of ocular examination in atypical forms of rickettsiosis.…”
Section: Introductionmentioning
confidence: 88%